19: Cost Analysis of Inpatient Treatment of Adolescents with Anorexia Nervosa: Hospital and Societal Perspectives. Issue 6 (1st June 2014) - Toulany, A; Wong, M; Katzman, DK; Akseer, N; Steinegger, C; Hancock-Howard, R; Coyte, PC
Abstract: BACKGROUND: Hospitalization is the treatment of choice for medically unstable adolescents with anorexia nervosa (AN). OBJECTIVES: The aim of this study was to determine the cost of inpatient treatment for adolescents with AN from both a hospital and societal perspective and to identify determinants of such costs. DESIGN/METHODS: Micro-costing methods were used for this retrospective cohort study of all adolescents (12 to 18 years) admitted for the first time with AN at a tertiary care child and adolescent eating disorder program in Toronto, Canada between September 1, 2011 and March 31, 2013. Demographic data and clinical variables were collected. Hospital administrative cost data and Canadian census data were used to calculate hospital and societal costs. Multivariate linear regression analyses were performed to identify significant predictors of hospital costs. RESULTS: Seventy-three adolescents were identified and included in this cost-analysis. Mean total hospital cost was $51, 349±26, 598 and mean total societal cost was $54, 932±27, 864 per admission, based on a mean length of stay of 37.9±19.7 days. Body mass index (BMI) was found to be a significant predictor of hospital costs (P=0.0002). For every unit increase in BMI there was a 15.7% decrease in hospital costs after controlling for time spent on the waiting list. Higher BMI (P<0.0001) and younger age (P=0.0480) at admission were both found to be significant negative predictors of caregiver costs after controlling for time spent on the waiting list. CONCLUSIONS: The economic burden of AN among adolescents is substantial. Younger age and lower BMIs were associated with increased hospitalization costs.